2021
DOI: 10.1001/jamaneurol.2020.4396
|View full text |Cite|
|
Sign up to set email alerts
|

Ticagrelor Added to Aspirin in Acute Ischemic Stroke or Transient Ischemic Attack in Prevention of Disabling Stroke

Abstract: IMPORTANCE Reduction of subsequent disabling stroke is the main goal of preventive treatment in the acute setting after transient ischemic attack (TIA) or minor ischemic stroke. OBJECTIVE To evaluate the superiority of ticagrelor added to aspirin in preventing disabling stroke and to understand the factors associated with recurrent disabling stroke. DESIGN, SETTING, AND PARTICIPANTS The Acute Stroke or Transient Ischemic Attack Treated With Ticagrelor and Aspirin for Prevention of Stroke and Death (THALES) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…The key findings reveal that DAPT appears to be safe and efficient in decreasing the risk of multiple ischemic strokes, particularly in the long term and with larger sample sizes ( 27 ), as well as being more effective than monotherapy in the early stages of acute ischemic stroke ( 24 ). This has also been confirmed by the most recent study by Amarenco et al ( 26 ), in which patients with TIA and minor ischemic stroke received ticagrelor in combination with aspirin to prevent disabling stroke or death at 30 days. The results showed that DAPT was more efficient than aspirin alone in decreasing the total burden of disability due to ischemic stroke recurrence.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The key findings reveal that DAPT appears to be safe and efficient in decreasing the risk of multiple ischemic strokes, particularly in the long term and with larger sample sizes ( 27 ), as well as being more effective than monotherapy in the early stages of acute ischemic stroke ( 24 ). This has also been confirmed by the most recent study by Amarenco et al ( 26 ), in which patients with TIA and minor ischemic stroke received ticagrelor in combination with aspirin to prevent disabling stroke or death at 30 days. The results showed that DAPT was more efficient than aspirin alone in decreasing the total burden of disability due to ischemic stroke recurrence.…”
Section: Resultssupporting
confidence: 59%
“…Dual therapy: aspirin plus ticagrelor—Amarenco et al ( 26 ) evaluated the combination of ticagrelor and aspirin (as opposed to aspirin alone) in stroke prevention. The main endpoint was the time to stroke (progression of the event or a new stroke) or death within 30 days.…”
Section: Resultsmentioning
confidence: 99%
“…There were significant lower rates of stroke or death (5.5% vs 6.6%, HR, 0.83; 95% CI 0.71 to 0.96; p=0.02) and ischaemic stroke (5.0% vs 6.3%, HR, 0.79; 95% CI, 0.68 to 0.93; p=0.004), but higher rate of severe bleeding (0.5% vs 0.1%, p=0.001) in the DAPT group. Exploratory analysis showed that ticagrelor plus aspirin was associated with lower rate of disabling stroke or death than aspirin alone (4.0% vs 4.7%, p=0.001) 36. For every 1000 patients, DAPT would prevent 11 strokes or deaths at the cost of four severe haemorrhages.…”
Section: Resultsmentioning
confidence: 97%
“…In ischemic stroke with ATF, treatment with ticagrelor could reduce the risk of recurrent ischemic stroke, but increase combination of major or minor bleedings (40). However, combination of ticagrelor and aspirin does not decrease the incidence of composite of stroke or death and disabling stroke compared with aspirin after ischemic stroke with ATF (41,42).…”
Section: Discussionmentioning
confidence: 99%